Fruits and Vegetables Availability for Human Consumption in Latin American and Caribbean Countries: Patterns and Determinants - Asfaw, Abay (2012)
Inadequate intake of fruits and vegetables (F&V) is one of the leading causes of chronic diseases in the world. This study examined the patterns and determinants of F&V availability for human consumption in Latin American and Caribbean countries between 1991 and 2002. The results showed that there were considerable disparities between and within countries and only one-third of the sampled countries (if only 20% wastage is assumed) could achieve the World Health Organization's recommendation of 146kg of F&V intake/capita/year. The elasticities estimated from a fixed effect regression also showed that income, urbanization, price, and poverty were some of the important factors that affect the long-term availability of F&V.